PENGARUH KOMPETENSI PEJABAT PENATAUSAHAAN KEUANGAN, SISTEM PENGENDALIAN INTERN PEMERINTAH, PENGAWASAN KEUANGAN DAERAH, SIKD DAN KUALITAS SDMTERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH KOTA DUMAI - Tengku Dea Monica; Taufeni Taufik; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the effect of the competence of the financial administration officials, the internal control system, the local finance supervision, regional financial information system and the quality of human resources to the value of the local government financial reporting information in Dumai. The technique used is purposive sampling. Respondents in this study is the Sub Division of Finance and Financial Staff. The sample used in this study were 66 respondents. Statistical methods are used to test hypothesis of the research is the analysis of multiple linier regression using the software spss version 22.0.The result of this study indicate that the variable areFinancial Administration Official Competence affect the value of the local government financial reporting information with a regression coefficient of 0.154 and 0.024 significant (alpha <0.05), internal control system of government influence on the value of the local government financial reporting information with a regression coefficient of 0.317 and 0.004 significant (alpha <0.05), the area of financial supervision affect the value of the local government financial reporting information with a regression coefficient of 0.599 and 0.001 significant (alpha <0.05), financial information systems area affect the value of government financial reporting information area with a regression coefficient of 0.221 and 0.046 significant (alpha <0.05), quality of human resources affect the value of the local government financial reporting information with a regression coefficient of 0.272 and 0.035 significant (alpha <0.05). The result of the coefficient of determination (R2) of 0.680 means that the contribution of independent variable influence to variable by 68% and the remaining 32% are influenced by other variables.Keywords: Information, financial administration, system of internal control, control of regional finance and quality of human resource